2022
DOI: 10.3390/ijms231911258
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Myrosinase with High Activity from Marine Bacterium Shewanella baltica Myr-37

Abstract: Myrosinase can hydrolyze glucosinolates to generate isothiocyanates, which have cancer prevention and anti-cancer properties. The main sources of myrosinase are cruciferous plants. To further improve the efficiency of isothiocyanates preparation, it is necessary to explore novel sources of myrosinases. In this study, we described a bacterium, Shewanella baltica Myr-37, isolated from marine mud, capable of producing a novel myrosinase (Smyr37) with a molecular weight of 100 kDa. The crude enzyme of Smyr37 showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…50 However, another study reported that MYR activity was decreased by adding both Zn 2+ and other metal ions such as Mg 2+ , Ag + and Fe 3+ . 51 In our results, we found that 0.5-10 mmol L −1 Zn 2+ decreased the total ITCs content in PRSP extract (see Supporting information, Fig. S3), suggesting that the properties of MYR are slightly different depending on the sources.…”
Section: Production Of Optimal Prsp Extractmentioning
confidence: 52%
See 1 more Smart Citation
“…50 However, another study reported that MYR activity was decreased by adding both Zn 2+ and other metal ions such as Mg 2+ , Ag + and Fe 3+ . 51 In our results, we found that 0.5-10 mmol L −1 Zn 2+ decreased the total ITCs content in PRSP extract (see Supporting information, Fig. S3), suggesting that the properties of MYR are slightly different depending on the sources.…”
Section: Production Of Optimal Prsp Extractmentioning
confidence: 52%
“…Especially, Zn 2+ has been reported to activate MYR activity in broccoli seed 49 or contribute to increasing the stability of SFEN in radish seed 50 . However, another study reported that MYR activity was decreased by adding both Zn 2+ and other metal ions such as Mg 2+ , Ag + and Fe 3+ 51 . In our results, we found that 0.5–10 mmol L −1 Zn 2+ decreased the total ITCs content in PRSP extract (see Supporting information, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The aliphatic GLSs of Col-0 had no effect on leaf bacterial community composition and in vitro growth on 4MSOB-GLS was slow and relatively poor. This could be because it was not degraded by the bacterial myrosinase, which are known to show substrate specificity ( 45 , 48 ). The success of R3 might also depend on formation and degradation of ITCs during bacterial GLS metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Sangkret et al found that the main elements affecting SFN production were myrosinase activity, temperature, pH, and reaction time [ 14 ]. Recently, researchers obtained a new myrosinase-producing bacterium from marine sediment (Marine Bacterium Shewanella baltica Myr-37) [ 58 ]. Once the reaction temperature is 40 °C and pH = 7.0, myrosinase can efficiently degrade sulforaphane to SFN in 25 min, the yield is 0.57 mg/mL, and the corresponding SFN conversion efficiency is 89%.…”
Section: Intestinal Microorganisms Can Enhance the Utilization Of Sfnmentioning
confidence: 99%